2015
DOI: 10.1159/000439381
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Dysfunction in Neonates Born to Mothers Who Have Undergone Hysterosalpingography Involving an Oil-Soluble Iodinated Contrast Medium

Abstract: Background/Aims: Patients developing neonatal thyroid dysfunction following maternal hysterosalpingography (HSG) involving the use of oil-soluble iodinated contrast medium (ethiodized oil) have been reported. The present study aimed to investigate the frequency and risk factors for neonatal thyroid dysfunction following HSG. Methods: We studied 212 infants born to mothers who had become pregnant after undergoing HSG involving the use of ethiodized oil. Results: Five of the 212 infants tested positive during co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 17 publications
2
49
1
Order By: Relevance
“…This may be owing to fluoroscopy screening or the reduced use of HSG with oil‐based contrast worldwide as HyCoSy and HyFoSy become more popular. Secondly, any concerns about the thyroid function of mother and child are based on the effects of iodinated contrast medium and a longer‐persisting time of oil‐based contrast in the pelvis. Maternal hypothyroidism can occur after tubal flushing with oil‐based contrast, especially in women with subclinical hypothyroidism before HSG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be owing to fluoroscopy screening or the reduced use of HSG with oil‐based contrast worldwide as HyCoSy and HyFoSy become more popular. Secondly, any concerns about the thyroid function of mother and child are based on the effects of iodinated contrast medium and a longer‐persisting time of oil‐based contrast in the pelvis. Maternal hypothyroidism can occur after tubal flushing with oil‐based contrast, especially in women with subclinical hypothyroidism before HSG.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal hypothyroidism can occur after tubal flushing with oil‐based contrast, especially in women with subclinical hypothyroidism before HSG. With regard to neonatal safety, a Japanese cohort showed that infants born to mothers undergoing HSG using oil‐based contrast before conceiving had a higher incidence of thyroid dysfunction (2.4%) than did the unselected population (0.7%). Although there is limited evidence on these safety issues, they should be fully discussed during clinical consultations.…”
Section: Discussionmentioning
confidence: 99%
“…According to their findings in the thyroid dysfunction group, the median dosage of ethiodized oil was significantly higher than in the normal thyroid function group. They recommended that when infertile women undergo HSG, the administrated dosage of oil-soluble iodinated contrast medium should be reduced to minimize the risk of thyroid dysfunction in fetus or neonates (57).…”
Section: Discussionmentioning
confidence: 99%
“…The mother had undergone hysterosalpingography after a second abortion at 34 years of age. Excessive maternal iodine intake due to iodinated contrast medium administration may cause hypothyroidism of the baby [ 11 ]. At 3 months of age, she received laser photocoagulation for retinopathy due to prematurity.…”
Section: Case Reportmentioning
confidence: 99%